A metal-catalyst-free oxidative coupling of anilines to aromatic azo compounds in water using bleach - Zuben, Theodora Von; Junior, Airton Salles; Souza, Gabriela de (Revista dos Trabalhos de Iniciação Científica da UNICAMP, 2019)
A simple route toward the synthesis of symmetrical and unsymmetrical aromatic azo compounds through oxidative coupling of anilines using widely available NaOCl is presented. This metal catalyst-free protocol is performed in water and affords the desired products in high yields.